Equity Crowdfunding: An Alternative Source of Financing Entrepreneurship in the Greater Accra Region of Ghana - Joseph Yensu; George Asumadu; Daniel Abayaakadina Atuilik; Kyei Baffour Asare (European Scientific Journal, ESJ, 2024)
Entrepreneurship is globally seen as a tool for job creation, contributing to the stability and economic development of nations. This is why the governments of many nations, including Ghana, put up initiatives to promote entrepreneurial activities. This paper focuses on assessing equity crowdfunding as an alternative source of generating fund for entrepreneurial projects in Ghana. A combination of qualitative and quantitative approaches were used in conducting this study in the Tema Municipality of the Greater Accra Region. A sample size of 149 entrepreneurs in various industries, 118 investors, and 90 respondents acting as both entrepreneurs and investors were chosen through purposive sampling method. Data were collected through the use of questionnaires and analyzed using descriptive statistics, employing tables and graphs. The results of the study showed that most entrepreneurs and investors had heard of equity crowdfunding but very few understood the operations of this type of funding. Also, it became evident that the investors and entrepreneurs had inadequate knowledge and understanding about crowdfunding adoption in Ghana. The study showed that equity crowdfunding is capable of bridging the funding gap and, therefore, is a suitable alternative in generating funds for entrepreneurship in Ghana. It is recommended that equity crowdfunding should be included as a source of funding in entrepreneurship curriculum. Also, policies should be made by government to establish regulations that will protect all the parties involved in equity crowdfunding.